2017
DOI: 10.1111/luts.12206
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of hyposensitivity of C‐fiber afferents at the proximal urethra in the development of urge urinary incontinence in patients with detrusor overactivity

Abstract: Hyposensitive C-fibers of the proximal urethra may contribute to the development of urodynamic DO as well as UUI in patients complaining of lower urinary tract symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Out of 80 studies, 61 exclusively applied CPTs [6,7,13–71], but four reported incomplete or no CPT results [14,32,61,64] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 80 studies, 61 exclusively applied CPTs [6,7,13–71], but four reported incomplete or no CPT results [14,32,61,64] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…In non-neurogenic overactive bladder (OAB) patients, results were more conflicting, as some studies demonstrated higher LUTCPTs in patients with OAB compared to controls [19,33], while other studies showed no difference [25,34] or decreased LUTCPTs [35]. Patients with stress urinary incontinence have been reported to show elevated CPTs compared to controls [36], with no difference compared to patients with OAB [25].…”
Section: Patients With Luts/lutdmentioning
confidence: 99%